Beans - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Festo Ngulu, an expert in plant disease, discusses land preparation and weed management, both chemical and manual, in the context of bean production.